Returns to Education and Earning Inequality Nexus: A Micro-Econometric Analysis for Pakistan - Sarwar, Ghulam; ., Muhammad Saeed Hashmi (Journal of Economics and Behavioral Studies, 2014)
This study investigates nexus between returns to education and earning inequality in Pakistan. The study utilizes quantile regression method to demonstrate how effect of different levels of education varies across conditional earning distribution. The results show that education plays a significant role in determination of within group earning inequality at all levels of education. Within group earning inequality is higher within the individuals having tertiary education as compared to the individuals having secondary and primary education. The earning inequality does not remain constant within the education groups during 2005-07. Moreover, education also causes earning inequality between educational groups. The findings of the study reveal that education has a positive effect on within as well as between groups earning inequality.